Multichannel Data Logger for Combat Vehicle - Antony Veera Puthira Raja, J; A. Bharath Raj, J; Bharath, M; C. Kishore Kumar, P; Rajendran, V (International Journal of Engineering and Technology, 2018)
The multichannel data logger is the one of the prominent component in any instrumentation system, the control process to give a high resolution to store accurate data from the sensing elements which varies depends on the different applications. In this point of view there are many developed data loggers are customized and general purpose data logger are available in the market with typical sampling frequency of 100 KHZ. Although the general purpose data logger with many of the time is suitable for laboratory level purpose when it comes to the defense, very special testing procedure based manufacturing process, larger channel sensing methods with a well-designed and adapted to specific application based customized data logger always been the under development. Proposed data logger is enabled with 8 channels IoT (Internet of things).Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â